3 - From Paternalism to Real Partnership with Local Communities? Experiences from Bwindi Impenetrable National Park (Uganda) - Namara, Agrippinah (Africa Development, 2006)
Conserving and sustainably managing Uganda’s wildlife and protected areas in partnership with neighbouring communities and other stakeholders for the benefit of the people of Uganda and the global community is the expressed mission of the Uganda Wildlife Authority. This article explores the form that conservation partnerships between the central government, local government and communities are taking in Uganda’s wildlife sector. Are these partnerships paving the way from the paternalistic approach to protected area management to partnerships between the wildlife authorities and local communities that are beneficial to both groups? To what extent are institutions representing the local community able to advance local interests and contribute to decision making on wildlife management within these partnerships? Are we moving towards democratic natural resource management? These are the questions that this article ponders.